The effects of counseling on fear of childbirth. (30th March 2015) - Larsson, Birgitta; Karlström, Annika; Rubertsson, Christine; Hildingsson, Ingegerd
<x xml:space="preserve">Abstract</x> Objective To investigate women's experiences of attending existing counseling programs for childbirth‐related fear and the effect of this counseling over time. Design A longitudinal survey. Setting Three hospitals in the central north of Sweden. Sample A selected sample of 936 women. Of these, 70 received counseling due to fear of childbirth (study‐group). Methods Data were collected with questionnaires 2 months and 1 year after giving birth with background data collected during midpregnancy. Comparisons were made between women with or without counseling. Crude and adjusted odds ratios (OR) were calculated. Main outcome measures Self‐reported childbirth fear, experience of counseling, birth experience and preferred mode of birth. Results Women in the counseling group reported higher childbirth fear 1 year after giving birth (OR 5.0, 95% confidence interval (95% CI) 2.6–9.3), they had a more negative birth experience that did not change over time (OR 2.1, 95% CI 1.2–3.9) and they preferred cesarean section to a greater extent (OR 12.0, 95% CI 5.1–28.1) in the case of another birth. Also, they were more often delivered by planned cesarean section (OR 4.7, 95% CI 2.4–9.1). However, 80% were satisfied with the given support. Conclusion Although women were satisfied with the treatment, this study shows that counseling had a minor effect on fear of childbirth, birth experiences or cesarean section rates. To help women with their fear of childbirth, more effective methods of treatment are needed.